Cognitive Outcomes in the Pragmatic Investigation of optimaL Oxygen Targets (CO-PILOT) trial: protocol and statistical analysis plan. Issue 11 (1st November 2022) - Mart, Matthew F; Semler, Matthew W; Bernard, Gordon; Casey, Jonathan D; Ely, E Wesley; Freundlich, Robert; Jackson, James C; Kiehl, Amy; Jenkins, Cathy; Wang, Guanchao; Lindsell, Christopher; Bryant, Patsy; et al.
Abstract : Introduction: Long-term cognitive impairment is one of the most common complications of critical illness among survivors who receive mechanical ventilation. Recommended oxygen targets during mechanical ventilation vary among international guidelines. Different oxygen targets during mechanical ventilation have the potential to alter long-term cognitive function due to cerebral hypoxemia or hyperoxemia. Whether higher, intermediate or lower SpO2 targets are associated with better cognitive function at 12-month follow-up is unknown. Methods and analysis: The P ragmatic I nvestigation of optimaL O xygen T argets (PILOT) trial is an ongoing pragmatic, cluster-randomised, cluster-crossover trial comparing the effect of a higher SpO2 target (target 98%, goal range 96%–100%), an intermediate SpO2 target (target 94%, goal range 92%–96%) and a lower SpO2 target (target 90%, goal range 88%–92%) on clinical outcomes in mechanically ventilated patients admitted to the medical intensive care unit at a single centre in the USA. For this ancillary study of long-term C ognitive O utcomes (CO-PILOT), survivors of critical illness who are in the PILOT trial and who do not meet exclusion criteria for CO-PILOT are approached for consent. The anticipated number of patients for whom assessment of long-term cognition will be performed in CO-PILOT is 612 patients over 36 months of enrolment. Cognitive, functional and quality of life assessments are assessed via telephone interview at approximately 12 months after enrolment in PILOT. The primary outcome of CO-PILOT is the telephone version of the Montreal Cognitive Assessment. A subset of patients will also complete a comprehensive neuropsychological telephone battery to better characterise the cognitive domains affected. Ethics and dissemination: The CO-PILOT ancillary study was approved by the Vanderbilt Institutional Review Board. The results will be submitted for publication in a peer-reviewed journal and presented at one or more scientific conferences.